The revised European social charter : an article by article commentary - Lukas, Karin (Elgar commentaries, 2021)
"This detailed Commentary explores the boundaries of social rights at a European level through analysis of the Revised European Social Charter (RESC), the most comprehensive regional document on social rights. The Commentary considers the treaty as the counterpart of the European Convention on Human Rights, examining how it sets out fundamental rights in the social field. It focuses primarily on the rich jurisprudence developed by the Charter's monitoring body, the European Committee of Social Rights (ECSR). Key features include: discussion of the application of social rights in practice examination of the implementation of the RESC in national law a guide to social rights and the corresponding human rights obligations of European states that have ratified the Charter analysis of economic, social and cultural rights in Europe across a range of areas including housing, health, education, employment, legal and social protection, migration and non-discrimination. Contributing to a deeper understanding of how state authorities and other human rights actors apply social rights in Europe, this Commentary will be an essential resource for academics and students of European law and human rights. Its presentation and analysis of the case law of the ECSR will also be beneficial for practitioners, lawmakers and human rights activists"--